Changes in soil physicochemical and microbial properties along elevation gradients in two forest soils. Issue 3 (2nd April 2016) - Hu, Lei; Xiang, Zeyu; Wang, Genxu; Rafique, Rashad; Liu, Wei; Wang, Changting
ABSTRACT: The effects of the interaction between tree species composition and altitude on soil microbial properties are poorly understood. In this study, soil samples (0–20 cm) were collected in August 2011 from Betula platyphylla and Picea crassifolia forests along two different altitudinal gradients. Soil microbial activity and biomass were measured using Biolog-ECO plates and phospholipid fatty acid analysis. Both of the forest soils were characterized by a significantly lower soil pH ( p  < .05) and higher soil organic matter (SOM) and nutrient levels (total nitrogen, available nitrogen and phosphorus) at higher altitudes compared with lower altitudes. Soil microbial activity was significantly lower in the birch forests ( p  < .05), but changed little in the spruce forests with increasing altitude. Soil microbial biomass decreased in the two forest soils across altitude gradients. With each 100-m drop in altitude, the soil microbial biomass exhibited a sharper decline in the spruce forests than in the birch forests. SOM had significant negative effects on soil microbial biomass, but no effects on soil microbial activity. Soil pH was significantly negative correlated with soil microbial biomass and activity. The tree species composition exhibited more negative effects on soil microbial biomass in the spruce forests, while altitude had a greater effect in the birch forests.